Burden of sickle cell trait and disease in the Uganda Sickle Surveillance Study (US3): a cross-sectional study - Grace Ndeezi, MBChB PhD; Charles Kiyaga, MSc MPhil; Arielle G Hernandez, BA; Deogratias Munube, MBChB; Thad A Howard, MS; Isaac Ssewanyana, MSc; Jesca Nsungwa, MBChB PhD; Sarah Kiguli, MBChB; Christopher M Ndugwa, MBChB; Dr. Russell E Ware, MD PhD; Jane R Aceng, MBChB MPH (Elsevier, 2016)
Background: Sickle cell disease contributes substantially to mortality in children younger than 5 years in sub-Saharan Africa. In Uganda, 20 000 babies per year are thought to be born with sickle cell disease, but accurate data are not available. We did the cross-sectional Uganda Sickle Surveillance Study to assess the burden of disease. Methods: The primary objective of the study was to calculate prevalence of sickle cell trait and disease. We obtained punch samples from dried blood spots routinely collected from HIV-exposed infants in ten regions and 112 districts across Uganda for the national Early Infant Diagnosis programme. Haemoglobin electrophoresis by isoelectric focusing was done on all samples to identify those from babies with sickle trait or disease. Findings: Between February, 2014, and March, 2015, 99 243 dried blood spots were analysed and results were available for 97 631. The overall number of children with sickle cell trait was 12 979 (13·3%) and with disease was 716 (0·7%). Sickle cell numbers ranged from 631 (4·6%) for trait and 23 (0·2%) for disease of 13 649 in the South Western region to 1306 (19·8%) for trait and 96 (1·5%) for disease of 6581 in the East Central region. Sickle cell trait was seen in all districts. The lowest prevalence was less than 3·0% in two districts. Eight districts had prevalence greater than 20·0%, with the highest being 23·9%. Sickle cell disease was less common in children older than 12 months or who were HIV positive, which is consistent with comorbidity and early mortality. Interpretation: Prevalence of sickle cell trait and disease were high in Uganda, with notable variation between regions and districts. The data will help to inform national strategies for sickle cell disease, including neonatal screening. Funding: Cincinnati Children's Research Foundation.